Current Situation of Illegal Usage of Special Expertise while Investigating Thefts - O. V. Haidar (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article has studied regulatory legal acts of Ukraine that regulate the usage of special expertise while investigating secret theft of another’s property. The concepts of “an expert”, “a specialist”, “a forensic inspector” have been revealed. The role of a specialist and an expert during the pre-trial investigation has been reflected. The author has analyzed the necessity of involving persons with special expertise during the conduction of the crime scene search in criminal proceedings on the fact of thefts. The functions of the forensic inspector while conducting the crime scene search have been considered. The author has revealed the essence of expert research conducted during the the crime scene search to investigate the secret theft of another’s property. Besides, the author has distinguished specific features of conducting the expert study of individual objects of the material situation at the crime scene and the expert study of the crime scene in the whole. The relevance of trasological research during the investigation of thefts on railway transport has been highlighted. Specific features of fingerprinting of victims during the investigation of thefts of personal property on railway transport have been provided. A number of examinations have been identified that can improve the investigation of thefts from vehicle. The author has analyzed the importance of interaction between the investigator and persons with special expertise during the investigation of thefts committed on the territory of horticultural associations and country house cooperatives. The need to conduct the crime scene search after the report of pickpocketing or attempted pickpocket has been revealed. The relevance of using special expertise while investigating pickpocketing has been highlighted. The research on the involvement of specialists while conducting examinations, searches in criminal proceedings on the fact of burglaries has been analyzed. The emphasis has been placed on the objects that should be initially examined during the investigation of the secret theft of someone else’s property, combined with the penetration into the premises. The importance of involving experts and specialists while preparing and conducting an investigative experiment has been studied. The necessity of appointing a commodity examination during the pre-trial investigation by the fact of the secret theft of someone else’s property has been revealed. The author has highlighted the role of a psychologist, teacher, physician as persons with special expertise.